2013
DOI: 10.1121/1.4822480
|View full text |Cite
|
Sign up to set email alerts
|

Inter-speaker articulatory variability during vowel-consonant-vowel sequences in twins and unrelated speakers

Abstract: The purpose of this study is to examine and compare the amount of inter-speaker variability in the articulation of monozygotic twin pairs (MZ), dizygotic twin pairs (DZ), and pairs of unrelated twins with the goal of examining in greater depth the influence of physiology on articulation. Physiological parameters are assumed to be very similar in MZ twin pairs in contrast to DZ twin pairs or unrelated speakers, and it is hypothesized that the speaker specific shape of articulatory looping trajectories of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The number of swallows (Rudney et al, 1995) and of words produced per day (Mehl et al, 2007) varies considerably between individuals. Moreover, the biomechanics of articulation (Weirich et al, 2013) and of swallowing (Kennedy et al, 2010) is characterized by substantial inter-individual variability. To investigate individual brain activity, we performed an independent component analysis (ICA) of individual taskbased FMRI data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The number of swallows (Rudney et al, 1995) and of words produced per day (Mehl et al, 2007) varies considerably between individuals. Moreover, the biomechanics of articulation (Weirich et al, 2013) and of swallowing (Kennedy et al, 2010) is characterized by substantial inter-individual variability. To investigate individual brain activity, we performed an independent component analysis (ICA) of individual taskbased FMRI data sets.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that part of inter-individual variability is indeed free rather than constrained by the physical, biological, linguistic or sociocultural environment is best evidenced by studies of speech produced by members of the same family. A number of studies have been published concerning monozygotic or dizygotic twin pairs, providing both similarities and differences in vocal tract and vocal source characteristics [3638]. In a recent study on vowel production in 10 pairs of French adult male siblings, [39] showed that the inter-individual acoustic variability was globally lower between brothers, compared with speakers that were not brothers.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies have revealed the existence of inter-speaker articulatory variability related to morphological differences between speakers and idiosyncratic articulatory strategies ( [5], [6]). It has been demonstrated that the inter-speaker variability partly corresponds to an adaptation to the morphology ( [7][8][9][10][11][12][13]). Other studies have also emphasised the relationships between speaker's strategy and morphology by means of articulatory normalisation ( [14], [15]), multi-speaker modelling aiming to uncover the common articulatory features ( [5], [16][17][18][19][20][21][22][23][24][25]), or sensitivity analysis of area function models [26].…”
Section: Introductionmentioning
confidence: 99%